Effect of Bacillus spp. as a biostimulant for Brassica oleracea var. capitata and Brassica oleracea var. sabellica microgreens - Gutiérrez-Chávez, Aldo (2025)
Introduction. The Bacillus genus has been used as a biostimulant with positive effects on crop yield and quality. However, there are few studies on its application in microgreens. Objective. To evaluate the effect of Bacillus subtilis (BsC4 and BsPC) and Bacillus thuringiensis (Bt24) as biostimulants on the germination and growth of red cabbage (Brassica oleracea var. capitata) and kale (Brassica oleracea var. sabellica) microgreens under controlled environmental conditions. Materials and methods. The study was conducted at the Universidad Autónoma de Chihuahua, Mexico, in 2023. Four treatments were assessed: Bt24, BsC4, BsPC, and seedlings without microorganisms (control) on red cabbage and kale seeds, under a completely randomized design (n = 5). Germination was monitored in the first trial, and microgreens development was assessed in the second. After 15 days, morphological variables, photosynthetic pigments, nitrate content, quality, and yield were measured. Data were analyzed using analysis of variance and Tukey’s tests (p < 0.05). Results. For kale, Bt24 improved germination speed (31.17 %) and reduced germination time (4.61 %), with no significant effect on red cabbage. In kale, yield increased (62.60 %) with Bt24, particularly in fresh biomass (63.3 %) and cotyledon area (61.57 %). In cabbage, BsC4 increased yield (44.31 %) and improved fresh biomass (42.21 %) and cotyledon area (50.57 %). Nitrate content was highest in kale with BsPC (138.30 %) and in red cabbage with Bt24 (65.14 %), while remaining within safe consumption limits. For visual quality, both crops achieved the “Good” and “Excellent” categories, with no differences between treatments. Conclusions. B. thuringiensis and B. subtilis could be used as growth biostimulants for cabbage and kale microgreens, offering a promising approach to optimize microgreen production under controlled environmental conditions.